2005
DOI: 10.1590/s1516-635x2005000300005
|View full text |Cite
|
Sign up to set email alerts
|

Response of broiler chickens to different dietary crude protein and feeding regimens

Abstract: Five isocaloric (3200kcal/kg) diets were used in an experiment designed to investigate the effects of dietary crude protein (CP) and feeding regimens on broiler performance. Day-old broilers were randomly distributed into four groups using a completely randomized design. Each group was replicated three times with ten broiler chicks per replicate. The experiment lasted for eight weeks. Broilers in group 1 received 23% CP from 0 to 3 weeks, 20% CP from 3 to 6 weeks and 18% CP from 6 to 8 weeks, while broilers in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
(7 reference statements)
1
2
0
Order By: Relevance
“…Analysis of lipid profile and glucose level in the blood serum of broiler meat for mice treated with different parts of the broiler meat: The biochemical analysis results indicated that the cholesterol, TG, LDL and HDL levels were remarkably higher Nonetheless the vitamin C contents were found to be very low. Protein contents are slightly higher than the standard value, a finding that is identical to earlier studies on chickenfeed materials (Oyedeji et al, 2005;Waldroup 2001). From Table 3, it is also observed that the crude fat content in all groups of meat sample was ranged from 26.18% to 29.05%, which was much higher than that documented in previous studies (Imaobong et al, 2015;Lonergan et al, 2003).…”
Section: Proximity Of Commercial Poultry (Broiler) Feed and Differentsupporting
confidence: 89%
“…Analysis of lipid profile and glucose level in the blood serum of broiler meat for mice treated with different parts of the broiler meat: The biochemical analysis results indicated that the cholesterol, TG, LDL and HDL levels were remarkably higher Nonetheless the vitamin C contents were found to be very low. Protein contents are slightly higher than the standard value, a finding that is identical to earlier studies on chickenfeed materials (Oyedeji et al, 2005;Waldroup 2001). From Table 3, it is also observed that the crude fat content in all groups of meat sample was ranged from 26.18% to 29.05%, which was much higher than that documented in previous studies (Imaobong et al, 2015;Lonergan et al, 2003).…”
Section: Proximity Of Commercial Poultry (Broiler) Feed and Differentsupporting
confidence: 89%
“…Differences in the digestibility of various feed brands employed in this study are in consonance with the reports of Uchegbu et al (2009). In contrast, Oyediji et al (2005) revealed that nutrient retention total protein level is a pointer to how changes in protein metabolism in the body affect growth rate, health status and meat yield (Adeyemo et al, 2000). Proteins are the major constituents of blood serum and they participate actively in various physiological functions including homeostasis of acid-base balance and colloid osmotic structure.…”
Section: Discussionmentioning
confidence: 99%
“…Excess dietary ME can lead to increased fat deposition and reduced carcass quality, while low CP diets can reduce the energy required to break down dietary protein and excrete excess amino acids, while improving nitrogen utilization and reducing nitrogen emissions ( Girish et al, 2013 ). Oyedeji et al (2005) suggested that 13.38 MJ/Kg is optimal for broiler chickens; while energy level is 12.96 MJ/Kg for broilers at 0 to 4 wk of age and 13.18 MJ/Kg at 4 to 8 wk of age ( Nahashon et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%